1996
DOI: 10.1007/bf00607280
|View full text |Cite
|
Sign up to set email alerts
|

MRI features of neurosurgical gossypiboma: report of two cases

Abstract: Retained surgical sponge is an uncommon complication in neurosurgical practice. We report two patients with retained surgical gauze and describe the clinical presentation and the characteristics of the foreign body on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Granulomas appear hypointense on T1-weighted and hyperintense on T2-weighted MRI images. If the lesion has capsule formation, it appears hypointense on both T1-and T2-weighted images (17)(18)(19)(20)(21). Textilomas may show an enhanced hyperintense rim around the hypointense centre after contrast medium administration.…”
Section: Discussionmentioning
confidence: 99%
“…Granulomas appear hypointense on T1-weighted and hyperintense on T2-weighted MRI images. If the lesion has capsule formation, it appears hypointense on both T1-and T2-weighted images (17)(18)(19)(20)(21). Textilomas may show an enhanced hyperintense rim around the hypointense centre after contrast medium administration.…”
Section: Discussionmentioning
confidence: 99%
“…), corticosteroid drugs, and spinal instrumentation. 2,3,[5][6][7][8][9][10][11][12][13][14][15][16] Treatment of spinal abscess caused by retained surgical sponges consists of early diagnosis, surgical removal, and appropriate antibiotic treatment if necessary. However, we believe that the presence of foreign material as a nidus for infection precludes successful treatment of a spinal infection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] A review of the literature concerning retained sponge following spinal surgery found only nine reports. 3,5,7,11,12,14,15) The incidence was reported as 0.7 per 10,000 patients but probably underestimates the actual incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Although the real incidence is unknown, it has been reported to be one in 3,000 to one in 5,000 cases of abdominal operations [1,2]. It has been reported to occur following surgical procedures such as abdominal, thoracic, cardiovascular, orthopedic, and even neurosurgical operations [3][4][5]. Because the symptoms of gossypiboma are usually nonspecific and may appear years after surgery, the diagnosis of gossypiboma may be difficult.…”
Section: Introductionmentioning
confidence: 99%